PENEGAKAN HUKUM TERHADAP TINDAK PIDANA PENYALAHGUNAAN PENGANGKUTAN DAN PERNIAGAAN BAHAN BAKAR MINYAK BERSUBSIDI DI WILAYAH HUKUM KABUPATEN BENGKALIS - Triana Lestari; Evi Deliana; Erdiansyah Erdiansyah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2020)
Bengkalis Regency is one of the regencies in Riau Province, Indonesia is the largest producer of petroleum which is the largest source of its regional budget along with gas. The criminal act of misuse of transportation and commerce of subsidized fuel which has occurred in Bengkalis Regency lately has become one of the cases that has taken a lot of public attention. This shows that the ineffectiveness of law enforcement's performance in tackling the misuse of transportation misuse and subsidized fuel business in the jurisdiction of Bengkalis Regency.This type of research can be classified in the type of sociological (empirical) legal research, because in this study the authors directly conduct research at the location or place of study in order to provide a complete and clear picture of the problem under study. This research was conducted in the jurisdiction of Bengkalis Regency. Data sources used are primary data and secondary data. Data collection techniques in this study were interviews and literature review.The conclusions that can be obtained from the results of the study are: First, law enforcement against the misuse of transportation misuse and subsidized fuel business in the jurisdiction of Bengkalis Regency is still not going well and there are still many criminal acts of fraud that occur. Second, the obstacles experienced in law enforcement against criminal acts of misuse and subsidized fuel trading in the Bengkalis Regency jurisdiction consist of factors of law enforcement officers, legal factors, facilities and facilities factors and community factors. Third, the efforts that can be made in overcoming the inhibiting factors in law enforcement against the misuse of transportation misuse and subsidized fuel business in the jurisdiction of Bengkalis Regency both preventive (preventive) and repressive (enforcement) are still not maximally carried out.Keywords: Law Enforcement, Crime, Abuse, Fuel, Subsidized